Odpowiedzi

Najlepsza Odpowiedź!
2009-11-25T16:59:56+01:00
*=do kwadratu
&=do trzeciej potęgi
^=do czwartej potęgi
#=do piątej potęgi

a) (a+3)(a-1)+(a-7)(a+5)=a*-a+3a-3+a*+5a-7a-35=2a*-38
b) (2b-5)(3-2b)-(3b+2)(b-6)=6b-4b*-15+10b-(3b*-18b+2b-12)=6b-4b*-15+10b-3b*+18b-2b+12=32b-7b*-15
c) -7c*(5c-4)+(3c*+c)(6-2c)=-35c&+28c*+18c*-6c&+6c-2c*=-41c&+44c*+6c
d) (-3d*-5d&)(2d*+3d)+(d&+4d*)(2d-2)=-6d^-9d&-10d#-15d^+2d^-2d&+8d&-8d*=-18d^-3d&-10d#-8d*
e) 3m(m-4)(5m+2)-m(2m+3)(4-3m)=3m*-12m(5m+2)-2m*-3m(4-3m)=3m*-60m*-24m-2m*-12m+9m=-55m*-27m -ale tego nie jestem pewna
f) -2x(3x-5y)-(x+2y)(3x-y)=-6x*+10xy-(3x*-xy+6xy-2y*)=-6x*+10xy-3x*+xy-6xy+2y*=-9x*+5xy+2y*
2009-11-25T17:11:31+01:00
A)=a²-a+3a-3+a²+5a-7a-35=
=2a²-38
b)=6b-4b²-15+10b-3b²-18b+2b-12=
=-7b-27
c)=-35c³+28c²+18c²-6c³+6c-2c²=
=-41c³=44c²+6c
d)=(-6d⁴-9d³-10d⁵-15d⁴+2d⁴-2d³+8d³-8d²)=
=-10d⁵-19d⁴-3d³-8d²
e)=3m(5m²+2m-20m-8)-m(8m-6m+12-9m)=
=15m³+6m²-60m²-24m-8m²+6m²-12m+9m²=
=15m³-47m²-36
f)=-6x²+10xy-3x²+xy+6xy-2y²=
=-9x²+17xy-2y²